The Impact of Future Climate Change on Wine Grape Revenues in the Pacific Northwest. - Fitzgerald, Ellen. (2017)
Abstract: Future climate change subjects the wine grape industry in the Pacific Northwest United States to considerable risk. I measure the impact of climate change on wine grape revenues in this region by looking at the historical effects of random fluctuations in weather on annual wine revenues using fine-scale (2.5 mile x 2.5 mile grid cells) daily data on temperature and precipitation from 1995-2005. The impact of future climate change on wine grape revenues is then estimated using county-level climate projections applied to my statistical estimates of the impact of weather on revenues. Projected impacts are supplemented by a dynamic forecasting analysis. Results show that by 2030 the premier growing regions in Northern California will face declining wine grape revenues. By 2050 and 2100, wine grape revenues in all growing regions are expected to fall, with many regions experiencing losses that exceed 20% of historical wine grape values.; Thesis (M.S.)--Tufts University, 2011.; Submitted to the Dept. of Economics.; Advisor: Gilbert Metcalf.; Committee: Jeffrey Zabel, Frank Ackerman, and Elizabeth Stanton.; Keywords: Economics, Climate Change, and Economics, Agricultural.